Comparison of Sertraline, Venlafaxine and Desipramine Effects on Depression, Cognition and the Daily Living Activities in Alzheimer Patients - Mokhber, N.; Abdollahian, E.; Soltanifar, A.; Samadi, R.; Saghebi, A.; Haghighi, M. B.; Azarpazhooh, A. (Pharmacopsychiatry, 2014)
Rationale: The effects of antidepressants on mood, cognition and the daily activities of Alzheimer patients are ambiguous. The effects of antidepressants SSRIs (serotonin specific reuptake inhibitors), TCAs (tricyclic antidepressants) and SNRIs (serotonin-norepinephrine reuptake inhibitors), in particular, are unknown.Objectives: This study aimed to compare the effects of sertraline, venlafaxine and desipramine on depression, cognition and the daily activities of Alzheimer patients.Methods: This randomized double-blind trial was approved by the Research and Ethics Committees of Mashhad University of Medical Sciences. 59 moderate Alzheimer patients with major depressive disorder were randomly divided into 3 groups (sertraline, venlafaxine and desipramine), treated for 12 weeks (150 mg maximum dose) and assessed by the Hamilton Depression Test (HRSD), the Mini Mental State Examination (MMSE) and the Barthel index at the week 0 and the 2nd, 4th, 8th, 12th weeks thereafter. Data were analyzed by SPSS software, using ANOVA and paired t-tests.Results: In the sertraline group, the results of all 3 tests, HRSD, MMSE and Barthel, in the 12th week showed significant improvements in comparison to the baseline (P<0.05 in all 3 tests). In the venlafaxine group, the results of MMSE and Barthel revealed significant improvements (P<0.05 in both tests). In the desipramine group, there was a significant improvement only in the Barthel test at the 12th week (P<0.05).Conclusion: In this trial, sertraline treatment was associated with superior effectiveness in relation to depressive, cognitive, and behavioral symptoms.
Keywords: Alzheimer’s disease (AD); antidepressants; dementia; cognition; depression